2022
DOI: 10.1177/23259671211073722
|View full text |Cite
|
Sign up to set email alerts
|

Inflation-Adjusted Medicare Reimbursement Has Decreased for Orthopaedic Sports Medicine Procedures: Analysis From 2000 to 2020

Abstract: Background: Decreases in Medicare reimbursement have been noted among many medical specialties. An in-depth analysis of the subspecialty of orthopaedic sports medicine is needed to determine changes in Medicare reimbursement in this field. Purpose/Hypothesis: The purpose was to elucidate the trends in inflation-adjusted Medicare reimbursement for orthopaedic sports medicine procedures between 2000 and 2020. It was hypothesized that Medicare reimbursement decreased substantially during the study period. Study D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This is slightly lower than the average reductions in reimbursement observed in orthopaedic sports medicine upper extremity and knee procedures with mean reductions of 31% and 34%, respectively. 18 However, these reductions for the upper extremity and knee sports medicine procedures were observed over a longer time frame from 2000 to 2020. Naturally, the overall reduction will be greater.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is slightly lower than the average reductions in reimbursement observed in orthopaedic sports medicine upper extremity and knee procedures with mean reductions of 31% and 34%, respectively. 18 However, these reductions for the upper extremity and knee sports medicine procedures were observed over a longer time frame from 2000 to 2020. Naturally, the overall reduction will be greater.…”
Section: Discussionmentioning
confidence: 95%
“…Our study found that the CAGR for hip arthroscopy procedures ranged from −1.74% to −2.18%, which is similar to the reported CAGR for shoulder/elbow (−2.3%) and knee procedures (−2.0%). 18 It is well-understood that hip arthroscopy typically has a longer surgical and setup time. Therefore, despite comparable yearly reductions in Medicare reimbursement, hip arthroscopic procedures may actually be experiencing a greater reduction in reimbursement by the hour.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have examined the trends in Medicare reimbursement for physicians, with a nearly universal decline in inflation-adjusted compensation for various orthopaedic procedures. 11,18,23,[26][27][28][29][30][31][32] Regarding spine surgery, a recent study by Haglin et al 10 found that all 15 procedures they examined experienced a notable decrease in inflation-adjusted reimbursement, with an average of 33.8% from 2000 to 2021. When doing a subanalysis on temporal trends, the average adjusted reimbursement rate for all procedures decreased by 23.4% from 2000 to 2010 and 15.6% from 2010 to 2021 (P , 0.0001).…”
Section: Ambulatory Surgical Center Trendsmentioning
confidence: 99%
“…An ongoing decline in Medicare physician reimbursement across most orthopaedic procedures has previously been identified [ [3] , [4] , [5] ]. Specifically, Haglin et al [ 3 ] found primary TKA surgeon reimbursement to decline by 41.9% when adjusting for inflation between 2000 and 2019.…”
Section: Introductionmentioning
confidence: 99%